Tuning Electronic Structure of CuCo2O4 Spinel via Mn‐Doping for Enhancing Oxygen Evolution Reaction. Issue 2 (23rd December 2022) - He, Xuanmeng; Qiao, Tong; Li, Beijun; Zhang, Zeqin; Wang, Shaolan; Wang, Xinzhen; Liu, Hui
Abstract: Cobalt‐based spinel oxide is a promising electrocatalyst for oxygen evolution reaction (OER) because of its low cost, excellent activity and stability. Herein, we designed the CuMnx Co2 O4 electrocatalyst with tunable electronic structure via Mn‐doping to enhance OER performance. Results showed that the CuMn0.5 Co2 O4 catalyst prepared by calcined at 600°C exhibited high crystalline without impurity phase, and possessed the enhanced Co 2+ /Co 3+ ratio and high concentration of oxygen vacancies, which were facilitated to enhance OER performance. Electrochemical test results showed the CuMn0.5 Co2 O4 catalyst had high OER performance with a low overpotential of 340 mV at the current density of 10 mA ⋅ cm −2 and a smaller Tafel slope of 69.8 mV ⋅ dec −1 . TOF and ECSA results illustrated that the more intrinsic catalytic activity on the CuMn0.5 Co2 O4 catalyst. After 1000 cycles, the catalyst exhibited high stability with the 8 1.7 % of current retention rate. The OER activity enhancement mechanism of was further analyzed, which were mainly ascribed to the conversion of variable Co 2+ /Co 3+ and enhanced oxygen vacancies. Abstract : Spinel Phase for Oxygen Evolution Reaction : The synthesized CuMn0.5 Co2 O4 catalyst possessed the enhanced Co 2+ /Co 3+ ratio and oxygen vacancies, enhancing absorption capacity of OH − and electron transport capacity, which improved OER performance of catalyst. The CuMn0.5 Co2 O4 catalyst exhibited high OER performance with a low overpotential of 340 mV at the current density of 10 mA ⋅ cm −2 and a smaller Tafel slope of 69.8 mV ⋅ dec −1 .